Disaster and the Ethics of Sympathy - David Dillard-Wright (In Medias Res, 2016)
Disasters promise to be a permanent feature of globalized, industrial society in the twenty-first century as economic divides combine with climate change to produce massive suffering and dislocation. At the same time as these global changes occur, the media landscape shifts to become fragmented and “monetized” across a variety of platforms. This article examines the impulse towards sympathy for others in this global milieu, in which it can become easy for people in developed nations to ignore the turmoil they experience through mass media. Coverage of disaster can become just another form of entertainment: in order to genuinely care for others, consumers of media must become active participants, working against the grain of information culture.